An Exploratory Study of Skin Problems Experienced by UK Nursing Home Residents Using Different Pad Designs. Issue 6 (November 2015) - Clarke-O'Neill, Sinead; Farbrot, Anne; Lagerstedt, Marie-Louise; Cottenden, Alan; Fader, Mandy
Abstract : PURPOSE: The primary aim of this study was to determine whether the severity of incontinence-associated dermatitis (IAD) among nursing home–based incontinence pad users varies between pad designs. A second aim was to examine the utility of a simple method for reporting skin health problems in which healthcare assistants were asked to record basic observational data at each pad change. STUDY DESIGN: Randomized, multiple crossover, observational, exploratory. SUBJECTS AND SETTING: Twenty-one men and 57 women using absorbent continence products to contain urinary and/or fecal incontinence were recruited from 10 nursing homes in London and the south of England. METHODS: A day-time variant and a night-time variant of each of the 4 main disposable pad designs on the market for moderate/heavy incontinence were tested: (1) insert pads with stretch pants; (2) 1-piece all-in-one diapers; (3) pull-up pants; and (4) belted/T-shape diapers. All pad variants for day-time use had an absorption capacity of 1900 mL ± 20% (measured using ISO 11948-1 International Standards Organization) while the capacity of night-time variants was 2400 mL ± 20%. Each resident used each of the 4 pad designs (day-time and night-time variants) for 2 weeks and the order of testing was randomized by nursing home. Skin health data were collected using 2 methods in parallel. Method 1 comprised visual observation by researchers (1 observation per pad design; 4 observations in total over 8 weeks). In method 2, healthcare assistants logged observational data on skin health at every pad change for the 8 weeks. The primary outcome variable was severity of the most severe skin problem noted by the researcher for each resident, and for each pad design (method 1). Descriptive data on skin care methods used in the nursing homes were also collected using short questionnaires and researcher observation. RESULTS: No significant differences in the severity or incidence of skin problems were found between observations using the 4 pad designs. However, a wide range of skin conditions was recorded that made classification difficult; the skin was often marked with creases from absorbent products, temporary marks, and pink/purple discoloration. We observed few cases of the severe erythema, rashes, and vesicles that are commonly used descriptors in previous skin tools. Nevertheless, the collected data reflect an abundance of skin problems that were difficult to categorize neatly. Researcher observations (method 1) showed that nearly all the residents (96%) had at least 1 IAD skin problem recorded over the 8-week period and 64% of residents had at least 1 problem that was rated as maximum severity. Healthcare assistants logged skin problems on 6.1% of pad changes. The discrepancy between researcher and healthcare assistant data appears to be largely due to healthcare assistants sometimes discounting low-grade IAD as normal for that population. CONCLUSION: Incontinence-associated dermatitis is common among nursing home residents who use incontinence pads, and it is often severe. No evidence was found that any design of pad was more likely than any others to be associated with skin problems. The method devised to enable healthcare assistants to record basic observational data on skin health in the diaper area at each pad change (Method 2) proved simple to use but still resulted in substantial underreporting of IAD, suggesting that further work is needed to develop a tool that more successfully encourages them to log and treat IAD problems. Abstract : The CE test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com/CE/JWOCN